Financial Analysis Tools in Local Government Units - Staszel, Anna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
Though LGU activities differ considerably from those of for-profit enterprises, financial analysis tools can prove immensely helpful in decision-making and in evaluating the broader performance of the LGUs. Using a number of indicators and interpreting them, the author seeks to show that the financial analysis of LGUs provides a range of useful information, not only for their management, but for all stakeholders with an interest in the efficiency and quality of LGU activities. The paper highlights the merits of conducting a financial analysis of local government units and presents the basic tools used for the analysis.